2011
DOI: 10.1021/nl200426g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation by Electrodeposition on Patterned Substrates (STEPS): A New Versatile Nanofabrication Method

Abstract: Arrays of high-aspect-ratio (HAR) nano- and microstructures are of great interest for designing surfaces for applications in optics, bio-nano interfaces, microelectromechanical systems, and microfluidics, but the difficulty of systematically and conveniently varying the geometries of these structures significantly limits their design and optimization for a specific function. This paper demonstrates a low-cost, high-throughput benchtop method that enables a HAR array to be reshaped with nanoscale precision by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 26 publications
1
76
0
5
Order By: Relevance
“…Growth and adhesion assays were carried out in static culture using M63 salts plus 0.5% (wt/vol) casamino acids and 0.2% (wt/vol) glucose (M63+). HEX substrates were cast in PDMS from a Bosch-etched silicon master, and feature sizes were varied using polypyrrole electrodeposition onto epoxynegative replicas of the silicon master, followed by PDMS casting (44). Biovolume was quantified using image analysis of confocal z stacks.…”
Section: Methodsmentioning
confidence: 99%
“…Growth and adhesion assays were carried out in static culture using M63 salts plus 0.5% (wt/vol) casamino acids and 0.2% (wt/vol) glucose (M63+). HEX substrates were cast in PDMS from a Bosch-etched silicon master, and feature sizes were varied using polypyrrole electrodeposition onto epoxynegative replicas of the silicon master, followed by PDMS casting (44). Biovolume was quantified using image analysis of confocal z stacks.…”
Section: Methodsmentioning
confidence: 99%
“…Many groups have fabricated engineered surface topography, using numerous fabrication techniques (soft lithography and double casting molding techniques, microcontact printing, electron beam lithography, nanoimprint lithography, photolithography, electrodeposition methods, etc.) [37][38][39][40][41][42][43][44][45][46][47] on a wide range of substrates, ranging from various polymeric materials (silicone, polystyrene, polyurethane, and epoxy resins) to metals and metal oxides (silicon, titanium, aluminum, silica, and gold) [21,40,45,[47][48][49][50][51][52][53][54][55]. Furthermore, engineered topography can be considered as part of a multi-faceted strategy to prevent biofouling, and could be combined with other methods such as surface chemical treatments, addition of antibiotics/bacteriostatic agents, etc.…”
Section: Surface Attachment and Biofilm Formationmentioning
confidence: 99%
“…These anisotropic arrays have found applications in unidirectional wetting, [ 24 , 192 ] anisotropic adhesion, [ 195 ] chemical and biological sensing, and actuation. [ 194 ] Kim et al demonstrated several approaches to make bent polymer nanohairs for applications in unidirectional wetting and dry adhesives. [ 195 ] First, they fabricated a silicon master template using lithography and dry etching (DRIE) as shown in Figure 27 a.…”
Section: Directed Mechanical Deformationmentioning
confidence: 99%